Impact of cool and warm water immersion on 50-m sprint performance in trained swimmers - Soultanakis, H.; Nafpaktitou, D.; Mandaloufa, S. (Journal of Sports Science & Medicine, 2012)
During competition, swimmers are many times required to swim repetitive events with limited rest in between. They often chose to rest either in or out of the water, in normal or warmer water temperature pools. The aim of this study was to elicuidate the effect of cool water (CWI), warm water (WWI) and no water immersion (NWI), on sprint swimming and performance variables in simulated competition conditions which demand high performance with short rest intervals. Methods: Eight well-trained swimmers (21± 2.4 years), after an initial warm up and a 15 min rest period performed two 50-m swimming sprints (S1 and S2) interspersed with a 15-min passive water immersion (head out) period in either cool water (26.7°C ) or warm water (30.0 °C). Both conditions took place within a 48 period and swimmers were randomly assigned to each condition using a cross-over design. Prior to S1 and S2, blood lactate concentration (([La]0 ), heart rate, strength (handgrip test) and flexibility (sit and reach test) were recorded. During S1 and S2, time, velocity, stroke rate and stroke length were either recorded or calculated. After S1 & S2, blood lactate concentration at 1 min ([La]1)and 3min ([La]3) were measured. Results:The statistical analysis revealed, a) no significant differences within and between any of the conditions between CWI, WWI and NWI in time, velocity, stroke rate and stroke length, and flexibility, b) a significant reduction of strength after only WWI (p=0.029), c) significantly higher lacate levels prior to sprinting ([La]0 ) after both WWI and CWI (p<001) when compared to NWI and d) most interstingly, a complete dissociation of swim performance times (sec) to starting blood lactate levels (R2=0.047; slope NS from zero). Conclusion: In conclusion, it appears that neither cool nor warm water immersion have any significant impact on performance and swimmers can exert maximally, despite physiological shifts associated to fatigue.